[177Lu]Lu-PSMA-617 (PluvictoTM): The First FDA-Approved Radiotherapeutical for Treatment of Prostate Cancer - Ute Hennrich; Matthias Eder (MDPI AG, 2022)
In March 2022, [177Lu]Lu-PSMA-617 (PluvictoTM) was approved by the FDA for the treatment of prostate cancer patients. Until now, the approval has been limited to patients with PSMA-positive metastatic castration-resistant prostate cancer who have previously received other therapy options (such as inhibition of the androgen receptor pathway and taxane-based chemotherapy). [177Lu]Lu-PSMA-617, which combines a PSMA-specific peptidomimetic with a therapeutical radionuclide, is used in a radioligand therapy that selectively delivers ionizing radiation to tumor cells, causing their death, while sparing the surrounding healthy tissue. In numerous clinical trials, the efficacy of [177Lu]Lu-PSMA-617 was demonstrated.